2005
DOI: 10.1124/jpet.105.092049
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTION: Opposite Effects of Pre- and Postischemic Treatments with Nitric Oxide Donor on Ischemia/Reperfusion-Induced Renal Injury

Abstract: We have demonstrated previously that preischemic treatment with FK409 [(Ϯ)-(E)-4-ethyl-2-[(E)-hydroxyimino]-5-nitro-3-hexenamide], a spontaneous nitric oxide (NO) donor, markedly improves ischemia/reperfusion-induced renal injury. However, there is conflicting information (renoprotective or cytotoxic) as to the contribution of NO to ischemic acute renal failure (ARF). In the present study, we investigated the effect of postischemic treatment with FK409 (1, 3, and 10 mg/kg i.v.) at 6 h after reperfusion on isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
(59 reference statements)
2
17
0
Order By: Relevance
“…NO has been shown to positively regulate all of these endothelial cell responses, thereby identifying this molecule as a prime agent with which to enhance angiogenesis (1,4). However, administration of NO can be problematic, with concerns over cellular toxicity, systemic pressor effects, ensuring tissue specificity, and delivery modalities being key conundrums (17)(18)(19). Recent studies have developed the concept that nitrite may act as a site-specific NO donor via mechanisms regulated by tissue hypoxia (25,26,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO has been shown to positively regulate all of these endothelial cell responses, thereby identifying this molecule as a prime agent with which to enhance angiogenesis (1,4). However, administration of NO can be problematic, with concerns over cellular toxicity, systemic pressor effects, ensuring tissue specificity, and delivery modalities being key conundrums (17)(18)(19). Recent studies have developed the concept that nitrite may act as a site-specific NO donor via mechanisms regulated by tissue hypoxia (25,26,29).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these observations, NO donors have been shown to have cardioprotective effects including augmentation of angiogenic responses in vitro and in vivo (9,(12)(13)(14)(15)(16)). However, a major limitation with the use of NO donors is that these agents are nonselective and may induce undesired consequences, including cellular injury to healthy tissue and systemic alterations in tissue perfusion (17)(18)(19). Taken together, these observations indicate that NO donor therapy would be very beneficial for therapeutic angiogenesis, yet at present there are no effective means to selectively deliver NO to ischemic tissues to promote angiogenesis.…”
mentioning
confidence: 94%
“…Renal O 2 . production was measured using a lucigenin-enhanced chemiluminescence assay as described previously (Nakajima et al, 2006). The whole kidney was removed from rats and cut into strips (2-mm pieces).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Yamasowa et al found that preconditioning prevents the decrease in endothelial nitric oxide synthase activity and prevented the increase in inducible nitric oxide synthase activity observed after 6 h of reperfusion. As Nakajima et al (2006) observed an increased production of superoxide in the first day after the ischemia, the inhibition of inducible nitric oxide synthase could theoretically prevent the formation of high levels of peroxynitrite. This could explain why inhibition of inducible nitric oxide synthase before the ischemia reduces renal ischemia/reperfusion injury (Chatterjee et al, 2002;Walker et al, 2000) and why inhibition of inducible nitric oxide synthase before the ischemia prevents renal microvascular hypoxia and inhibition of endothelial isoform aggravates renal function (Legrand et al, 2009).…”
Section: Ischemic Preconditioningmentioning
confidence: 99%
“…The data of these studies indicate that preconditioning protects the kidney partly by increasing nitric oxide levels due to the increase in endothelial (early protecting effect) or in the inducible nitric oxide synthase activity (long lasting protective effect). The studies of Nakajima et al (2006) who observed a significant attenuation of nitrotyrosine formation, neutrophil infiltration into renal tissues, and renal superoxide production, that were significantly attenuated by the preischemic treatment with a nitric oxide donor. Thus, a better understanding of ischemic preconditioning may help to unravel the underlying mechanisms of protection that mediate this tolerance against injury.…”
Section: Ischemic Preconditioningmentioning
confidence: 99%